High-ground-temperature-resistant ultrahigh-flow nano-modified polymer grouting material as well as preparation method and application thereof
By using tannin acid and cellulose nanofibers in the grouting material to regulate the hydration process and fluidity, the problem of difficult to regulate the gelation time of grouting materials and reduced fluidity in deep high ground temperature environments is solved, and efficient grouting diffusion and reinforcement effects are achieved.
Patent Information
- Application Number
- CN202411979211.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-31
AI Technical Summary
In deep high ground temperature environments, the gelling time of conventional grouting materials is difficult to regulate, and the fluidity is reduced, resulting in a narrowing of the grouting diffusion range, and the material is prone to cracking at high temperatures, affecting the reinforcement effect.
A high-temperature-resistant ultra-high flow nanomodified polymer grouting material is used. This material consists of cement, fly ash, silica fume, calcium hydroxide, sodium carbonate, tanninic acid and cellulose nanofibers. Through the bridging effect of tanninic polyphenol hydroxyl groups and cellulose nanofibers, the hydration process and fluidity are regulated and the gelling time is extended.
This material can maintain high fluidity in high ground temperature environments, expand the grouting diffusion range, and achieve precise control of gelling time, avoid material cracking and improve reinforcement effect.
Smart Images

Figure CN119683918A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of geotechnical engineering, and in particular relates to a high ground temperature resistant ultra-high flow nano-modified polymer grouting material and a preparation method and application thereof. Background Art
[0002] As shallow mineral resources are exhausted, resource development is gradually moving to the deep earth. For example, the mining depth of coal mines has reached 1500m, and the mining depth of metal mines has exceeded 4350m. The mining depth of metal and non-metallic mineral resources continues to increase, and the temperature of the surrounding rock of mine shafts and tunnels increases by (1-3)℃ / 100m. The high geothermal environment causes the failure of conventional grouting materials and greatly reduces the anti-seepage effect of grouting reinforcement. It is very easy to induce major disasters such as landslides, roof falls, water inrush, and mud inrush, which seriously threatens the safety and stability of mine shaft and tunnel lifeline projects.
[0003] High geothermal environment induces slurry thickening and viscosity, greatly reducing the diffusion and reinforcement range of deep rock mass grouting, and at the same time affects the hydration process of slurry, which brings severe challenges to the research and development of grouting materials and performance control. In order to ensure the anti-seepage effect of grouting reinforcement of deep high geothermal rock mass, it is urgent to regulate the gelling properties and fluidity of grouting materials. At present, commonly used grouting materials include cement and cement-water glass two-liquid slurry, which tend to solidify quickly in high temperature environment, reduce fluidity, and are prone to cracking and rapid strength decline after solidification. Especially under high geothermal conditions, the setting time of cement-water glass two-liquid slurry is too short, which easily leads to blockage of grouting holes. In addition, the slurry may present an unstable jelly or tofu dregs shape after solidification, which seriously weakens the effect and scope of deep rock mass grouting reinforcement. In order to overcome these limitations, it is usually necessary to add specific admixtures to improve the performance of grouting materials. These admixtures can prolong the setting time, improve the fluidity and stability of the slurry, and thus expand the diffusion effect of grouting materials in high temperature environments.
[0004] At present, there are many kinds of admixtures widely used to control the fluidity and gelation time of cementitious materials, such as sodium gluconate, citric acid, tartaric acid, boric acid and sucrose. To a certain extent, the retarding grouting material has higher fluidity and wider diffusion range. Its retarding effect mainly depends on the internal groups, which are ranked from strong to weak as follows: carbon-hydrogen bond < polyol chain (C n H 2n+2 - x (OH))<sulfonic acid group (-SO 3 H)≈carboxyl (-COOH)<phosphate (-PO 3 H 2)≈hydroxyl (-OH)<carboxyl phosphate, it can be found that the retarding effect of carboxyl is not ideal, so polycarboxylic acid and other water reducers whose main groups are carboxyl groups cannot be widely used in high-temperature grouting materials. Among the commonly used retarders, the main groups inside sodium gluconate, citric acid, and tartaric acid are also carboxyl groups, and their retarding effects are worse than those of hydroxyl retarders. Although the internal groups of sucrose are hydroxyl groups, the number of hydroxyl groups contained in it is relatively small, so its high temperature resistance is weaker. The main groups inside boric acid are hydroxyl (-OH) and boron oxygen bond (BO). The boron atom in the boric acid molecule is connected to three hydroxyl groups to form a trihydroxyborate (B(OH) 3 ), so it contains fewer hydroxyl groups and has worse high temperature resistance. The above admixtures can improve the gel time and fluidity of grouting materials to a certain extent, but they still cannot meet the ultra-high performance requirements of deep high geothermal environments, making them unable to be widely used in deep engineering.
[0005] Therefore, there is an urgent need to develop a high-performance grouting material in this field to solve the problem of grouting diffusion and gelation regulation in deep high-temperature surrounding rocks. Summary of the invention
[0006] In view of the difficulty of grouting diffusion in deep high-temperature surrounding rocks and the difficulty in regulating the gelling time of materials, the present invention proposes a high-temperature resistant ultra-high-flow nano-modified polymer grouting material and its preparation method and application. The grouting material can maintain high fluidity for a long time in a high-temperature environment, effectively expand the grouting diffusion range, and can achieve precise regulation of the gelling time of the grouting material. At the same time, high-mass fraction fly ash and silica ash are stimulated to produce calcium silicate aluminate hydration products, which solves the shortcomings of conventional calcium silicate grouting cementing materials in high-temperature environments, such as poor reinforcement and anti-seepage effect and easy cracking of slurry.
[0007] To achieve the above object, the present invention provides the following technical solutions:
[0008] One of the technical solutions of the present invention:
[0009] The invention provides a high ground temperature resistant ultra-high fluidity nano modified polymer grouting material, wherein the raw material contains tannic acid and cellulose nano fibers at the same time.
[0010] The high ground temperature resistant ultra-high flow nano-modified polymer grouting material is composed of the following raw materials: cement, fly ash, silica fume, calcium hydroxide, sodium carbonate, tannic acid, cellulose nanofibers and water;
[0011] In terms of weight percentage, based on the weight of cement, the dosage of other components is as follows:
[0012] The amount of fly ash added is 70%-80% of the weight of cement.
[0013] The amount of silica fume added is 7%-10% of the weight of cement.
[0014] The dosage of tannic acid is 0.2%-0.4% of the weight of cement.
[0015] The amount of cellulose nanofiber added is 0.08%-0.25% of the weight of cement.
[0016] The dosage of calcium hydroxide is 6%-9% of the weight of cement.
[0017] The dosage of sodium carbonate is 3%-5% of the weight of cement;
[0018] The water-cement ratio is 0.5.
[0019] Preferably, the amount of tannic acid added is 0.2%-0.3% of the weight of cement, and the amount of cellulose nanofiber added is 0.08%-0.16% of the weight of cement.
[0020] More preferably, the amount of tannic acid added is 0.3% by weight of cement, and the amount of cellulose nanofiber added is 0.16% by weight of cement.
[0021] Too high a dosage of tannic acid will result in a long coagulation time or even no coagulation, resulting in low strength in the later stage; too low a dosage will result in the failure to play the best role, the coagulation time will be shortened, and the cellulose nanofibers will not be fully dispersed, resulting in agglomeration.
[0022] When the cellulose nanofiber dosage is too high, due to the large specific surface area and hydroxyl groups of the cellulose nanofiber itself, it has a strong water absorption capacity, which reduces the early fluidity and makes it unable to meet the grouting requirements; when the dosage is too low, due to the insufficient cellulose nanofiber dosage, the bridging effect provided is not obvious, which leads to a low improvement in the later strength, resulting in the inability to suppress the development of cracks after injection, and may even cause further improvement of cracks due to its own shrinkage.
[0023] The present invention uses cement, fly ash and silica fume, tannic acid and cellulose nanofibers to prepare high ground temperature resistant ultra-high flow nano-modified polymer grouting materials. The innovation lies in: first, tannic acid itself has multiple phenolic hydroxyl groups, and these hydroxyl molecules can form intramolecular or intermolecular hydrogen bonds, making it difficult to decompose at high temperatures, thereby making it have strong high temperature stability, so that it can better adapt to high temperature environments; secondly, tannic acid itself has more pyrogallol groups, which can be adsorbed on Ca in a covalent or non-covalent manner. 2+ surface or with Ca 2+Complexation occurs to generate TA-Ca, which slows down the hydration rate inside the cement, thereby maintaining a high fluidity for a long time and achieving a slow setting effect; finally, tannic acid itself is amphiphilic, that is, part of the molecule is hydrophilic (such as hydroxyl) and the other part is hydrophobic (such as benzene ring). This amphiphilic property enables tannic acid to form a stable adsorption layer on the surface of nanoparticles, reducing the interaction between particles and promoting dispersion. The agglomeration of cellulose nanofibers after dispersion is weakened, making them more evenly dispersed. At the same time, because cellulose nanofibers have a long aspect ratio, that is, the fiber length is much longer than the diameter, it can cross microcracks and pores in the cementing matrix to form an effective bridge, thereby preventing the cementing particles from being destroyed under pressure, thereby achieving the purpose of improving the plugging effect. In addition, the calcium aluminosilicate hydration products produced by stimulating high mass fraction fly ash and silica fume are more stable and less prone to shrinkage and cracking in high ground temperature environments.
[0024] The second technical solution of the present invention:
[0025] The present invention also provides a method for preparing the high ground temperature resistant ultra-high flow nano-modified polymer grouting material, comprising the following steps:
[0026] S1. Accurately weigh the raw materials according to the ratio, dry mix the cement, fly ash and silica fume, so that the three substances are evenly mixed to obtain a composite cementing base material for grouting material;
[0027] S2. Divide the water into three equal parts, mix 1 / 3 of the water and tannic acid, stir evenly, and obtain a tannic acid solution;
[0028] S3. Mix 1 / 3 of the water with the cellulose nanofibers and stir evenly to obtain a cellulose nanofiber solution;
[0029] S4. The cellulose nanofiber solution and the tannic acid solution are stirred evenly, and after stirring, the mixture is allowed to stand to obtain a first mixed solution, so that the tannic acid can be adsorbed on the surface of the cellulose nanofibers to reduce the interaction between the particles, thereby promoting further dispersion of the cellulose nanofibers;
[0030] S5. Mix 1 / 3 of water, sodium carbonate and calcium hydroxide to obtain a second mixed solution. The sodium carbonate and calcium hydroxide react to generate sodium hydroxide and calcium carbonate. At the same time, due to the high content of calcium hydroxide, there will be residual calcium hydroxide. The sodium hydroxide and calcium hydroxide generated by the reaction act as alkali activators to improve the reaction activity of the internal fly ash. At the same time, calcium hydroxide can also provide a calcium source to promote the formation of C(N)-ASH. The generated calcium carbonate can fill the pores inside the cement on the one hand, and on the other hand, it can also undergo electrolysis to become calcium ions and carbonate ions to generate calcium aluminate. Since the decomposition temperature of calcium aluminate is higher than that of calcium sulfoxide, it helps to improve the high temperature resistance of the grouting material;
[0031] S6. Pour the first mixed solution and the second mixed solution into the composite cementitious base material, stir evenly, and obtain a high ground temperature resistant ultra-high flow nano-modified polymer grouting material.
[0032] In step S2, the stirring rate is 300 rpm and the stirring time is 2 min.
[0033] In step S3, the stirring rate is 500 rpm and the stirring time is 2 min. The cellulose nanofibers are initially dispersed by high-speed stirring, so that tannic acid can be more easily adsorbed on their surface in the subsequent process.
[0034] In step S4, the stirring rate is 300 rpm and the stirring time is 2 min;
[0035] In step S5, the stirring rate is 300 rpm and the stirring time is 2 min.
[0036] In step S6, the stirring rate is 300 rpm and the stirring time is 4 min.
[0037] The third technical solution of the present invention:
[0038] The present invention also provides the use of the high geothermal resistant ultra-high flow nano-modified polymer grouting material in surrounding rock grouting under a high geothermal environment, wherein the high geothermal environment is 40-80°C.
[0039] Compared with the prior art, the present invention has the following advantages and technical effects:
[0040] The present invention uses composite silicate cement, fly ash and silica fume as base materials, and coordinates calcium hydroxide, sodium carbonate, cellulose nanofibers and tannic acid to regulate their hydration process, fluidity and mechanical strength, and injects nano-modified cementing particles into deep surrounding rocks, which can maintain high fluidity for a long time in a high ground temperature environment, effectively expand the grouting diffusion range, and achieve precise regulation of the gelling time of the grouting material. At the same time, high-mass fraction fly ash and silica fume are stimulated to produce calcium silicate aluminate hydration products, which solves the shortcomings of the current conventional calcium silicate grouting cementing materials, such as poor reinforcement and anti-seepage effect and easy cracking of the slurry in a high ground temperature environment. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:
[0042] Figure 1 This is the silicate hydration and aluminosilicate polymerization process in Comparative Example 7 without tannic acid and cellulose nanofibers;
[0043] Figure 2 The silicate hydration and aluminosilicate polymerization process when tannic acid and cellulose nanofibers are added in Example 1;
[0044] Figure 3 The diagram is the mechanism of tannic acid in single cemented particles;
[0045] Figure 4 The diagram is the mechanism of tannic acid in multi-cemented particles;
[0046] Figure 5 The XRD images of Example 1 at different curing ages and different admixtures when the curing temperature is 20°C;
[0047] Figure 6 The XRD images of Example 2 at different curing ages and different admixtures when the curing temperature is 50°C;
[0048] Figure 7 The XRD images of Example 3 at different curing ages and different admixtures when the curing temperature is 80°C;
[0049] Figure 8 The cumulative porosity curve of the grouting material slurry when the curing temperature is 20°C in Example 1;
[0050] Fig. 9 The internal pore distribution of the grouting material when the curing temperature is 20°C in Example 1;
[0051] Fig.10 The cumulative porosity curve of the grouting material slurry when the curing temperature is 50°C in Example 2;
[0052] Fig.11 The internal pore distribution of the grouting material when the curing temperature is 50°C in Example 2;
[0053] Fig.12 The cumulative porosity curve of the grouting material slurry when the curing temperature is 80°C in Example 3;
[0054] Fig.13 The internal pore distribution of the grouting material when the curing temperature is 80°C in Example 3;
[0055] Fig.14 This is a SEM image of the grouting material prepared in Comparative Example 1 when the curing age is 3 days;
[0056] Fig.15 This is a SEM image of the grouting material prepared in Comparative Example 2 when the curing age is 3 days;
[0057] Fig.16 This is a SEM image of the grouting material prepared in Example 1 when the curing age is 3 days;
[0058] Fig.17 This is a SEM image of the grouting material prepared in Comparative Example 3 when the curing age is 3 days;
[0059] Fig.18 This is a SEM image of the grouting material prepared in Comparative Example 4 when the curing age is 3 days;
[0060] Fig.19 This is a SEM image of the grouting material prepared in Example 2 when the curing age is 3 days;
[0061] Fig. 20 This is a SEM image of the grouting material prepared in Comparative Example 5 when the curing age is 3 days;
[0062] Fig.21 This is a SEM image of the grouting material prepared in Comparative Example 6 when the curing age is 3 days;
[0063] Fig. 22 This is a SEM image of the grouting material prepared in Example 3 when the curing age is 3 days;
[0064] Fig.23 This is the SEM image of the calcium sulfide on the surface of the aluminum-rich material (fly ash) in Example 3 when the curing age is 3 days. DETAILED DESCRIPTION
[0065] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0066] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0067] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0068] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0069] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0070] The embodiment of the present invention provides a high ground temperature resistant ultra-high flow nano-modified polymer grouting material, which is composed of the following raw materials: cement, fly ash, silica fume, calcium hydroxide, sodium carbonate, tannic acid, cellulose nanofibers and water;
[0071] In terms of weight percentage, based on the weight of cement, the dosage of other components is as follows:
[0072] The amount of fly ash added is 70%-80% of the weight of cement.
[0073] The amount of silica fume added is 7%-10% of the weight of cement.
[0074] The amount of tannic acid added is 0.2%-0.4% of the weight of cement, preferably 0.2%-0.3% of the weight of cement, more preferably 0.3% of the weight of cement.
[0075] The amount of cellulose nanofiber added is 0.08%-0.25% by weight of cement, preferably 0.08%-0.16% by weight of cement, more preferably 0.16% by weight of cement.
[0076] The dosage of calcium hydroxide is 6%-9% of the weight of cement.
[0077] The dosage of sodium carbonate is 3%-5% of the weight of cement;
[0078] The water-cement ratio is 0.5;
[0079] The preparation method of the above grouting material is as follows:
[0080] S1. Accurately weigh the raw materials according to the ratio, dry mix the cement, fly ash and silica fume, so that the three substances are evenly mixed to obtain a composite cementing base material for grouting material;
[0081] S2. Divide the water into three equal parts, mix 1 / 3 of the water and tannic acid, stir evenly, stir at a rate of 300 rpm, stir for 2 min, and obtain a tannic acid solution;
[0082] S3. Mix 1 / 3 of water with cellulose nanofibers and stir evenly at a stirring rate of 500 rpm for 2 min to obtain a cellulose nanofiber solution. The cellulose nanofibers are initially dispersed by high-speed stirring so that tannic acid can be more easily adsorbed on their surface in the subsequent process.
[0083] S4. The cellulose nanofiber solution and the tannic acid solution were stirred uniformly at a stirring rate of 300 rpm for 2 min, and the mixture was allowed to stand for 3 min to obtain a first mixed solution, so that the tannic acid could be adsorbed on the surface of the cellulose nanofibers to reduce the interaction between the particles, thereby promoting further dispersion of the cellulose nanofibers;
[0084] S5. Mix 1 / 3 of water, sodium carbonate and calcium hydroxide, stirring at a rate of 300rpm for 2 minutes to obtain a second mixed solution. Sodium carbonate and calcium hydroxide can react to generate sodium hydroxide and calcium carbonate after mixing. At the same time, due to the high content of calcium hydroxide, there will be residual calcium hydroxide. The sodium hydroxide and calcium hydroxide generated by the reaction act as alkali activators to improve the reaction activity of the internal fly ash. At the same time, calcium hydroxide can also provide a calcium source to promote the formation of C(N)-ASH. The generated calcium carbonate can fill the pores inside the cement on the one hand, and on the other hand, it can also undergo electrolysis to become calcium ions and carbonate ions to generate calcium aluminate. Since the decomposition temperature of calcium aluminate is higher than that of calcium sulfoxide, it helps to improve the high temperature resistance of the grouting material;
[0085] S6. Pour the first mixed solution and the second mixed solution into the composite cementing base material and stir evenly at a stirring rate of 300 rpm for 4 minutes to obtain a high ground temperature resistant ultra-high flow nano-modified polymer grouting material.
[0086] S7. Place the prepared grouting materials into curing boxes with different curing temperatures for curing to simulate a high ground temperature environment, and take them out after a corresponding period of time for subsequent experiments.
[0087] The high ground temperature resistant ultra-high flow nano-modified polymer grouting material provided by the embodiment of the present invention can be used for surrounding rock grouting in a high ground temperature environment of 20-80°C.
[0088] In an embodiment of the present invention, the curing temperature of the grouting material is benchmarked against the high geothermal environment of deep earth engineering. There are two common grouting methods, namely direct grouting method and pipeline grouting method. The direct grouting method is to bring the grouting material into the grouting position and inject it into the pores using equipment such as a grouting pump, that is, the temperature of the slurry when injected is the formation temperature. In the pipeline grouting method, a pipeline system is established on the surface, and then the grouting material is transported to the corresponding pores through the pipeline, that is, the temperature of the injected slurry is the temperature of the ground surface temperature slowly rising to the formation temperature, and there is a temperature rise curve. Since the higher the temperature, the faster the viscosity of the grouting material increases, when the grouting requirements are met under high temperature conditions, the grouting requirements when slowly rising from ground temperature to high temperature must also be met, so the grouting material of the present invention can be applied to high geothermal environments.
[0089] All raw materials used in the embodiments of the present invention and the comparative examples are purchased from the market. As an example, cement is P.O42.5 cement purchased from Zhucheng Yangchun Cement Co., Ltd.; silica fume is 96-grade silica fume purchased from Hengyuan New Materials Co., Ltd.; fly ash is the third-grade fly ash (325 mesh) selected from Yixiang New Materials Co., Ltd.; cellulose nanofiber is a hydrogel solution purchased from Zhongshan Nanofiber Co., Ltd., with a mass percentage content of 2.5%; tannic acid is purchased from Tianjin Zhonglian Chemical Reagent Co., Ltd.; calcium hydroxide is purchased from Tianjin Huasheng Chemical Reagent Co., Ltd.; sodium carbonate is anhydrous sodium carbonate purchased from Tianjin Juhengda Chemical Co., Ltd.
[0090] Since the cellulose nanofibers directly purchased are in the form of a hydrogel solution and are not easy to use due to their large aspect ratio, the cellulose nanofibers are dissolved in water before use in the present invention to facilitate subsequent use.
[0091] In the present invention, the water-cement ratio is the weight ratio of the amount of water to the amount of cement, and is usually expressed by the formula: water-cement ratio=weight of water / weight of cement.
[0092] In the present invention, "parts" are "parts by weight" unless otherwise specified.
[0093] The technical solution of the present invention is further illustrated by the following embodiments.
[0094] Example 1
[0095] This embodiment provides a high temperature resistant ultra-high flow nano-modified polymer grouting material and a preparation method thereof. The grouting material is made of the following raw materials in parts by weight:
[0096] 500 parts of cement, 375 parts of fly ash, 42.5 parts of silica fume, 37.5 parts of calcium hydroxide, 20 parts of sodium carbonate, 1.5 parts of tannic acid, 0.8 parts of cellulose nanofiber, and a water-cement ratio of 0.5.
[0097] The preparation method of the above grouting material is as follows:
[0098] S1. Accurately weigh the raw materials according to the ratio, dry mix the cement, fly ash and silica fume, so that the three substances are evenly mixed to obtain a composite cementing base material for grouting material;
[0099] S2. Divide the water into three equal parts, mix 1 / 3 of the water and tannic acid, stir evenly, stir at a rate of 300 rpm, stir for 2 min, and obtain a tannic acid solution;
[0100] S3. Mix 1 / 3 of water with cellulose nanofibers and stir evenly at a stirring rate of 500 rpm for 2 min to obtain a cellulose nanofiber solution. The cellulose nanofibers are initially dispersed by high-speed stirring so that tannic acid can be more easily adsorbed on their surface in the subsequent process.
[0101] S4. The cellulose nanofiber solution and the tannic acid solution were stirred uniformly at a stirring rate of 300 rpm for 2 min, and the mixture was allowed to stand for 3 min to obtain a first mixed solution, so that the tannic acid could be adsorbed on the surface of the cellulose nanofibers to reduce the interaction between the particles, thereby promoting further dispersion of the cellulose nanofibers;
[0102] S5. Mix 1 / 3 of water, sodium carbonate and sodium hydroxide at a stirring rate of 300rpm for 2 minutes to obtain a second mixed solution. Sodium carbonate and calcium hydroxide react to generate sodium hydroxide and calcium carbonate. At the same time, due to the high content of calcium hydroxide, there will be residual calcium hydroxide. The sodium hydroxide and calcium hydroxide generated by the reaction act as alkali activators to enhance the reaction activity of the internal fly ash. At the same time, calcium hydroxide can also provide a calcium source to promote the formation of CSH. The generated calcium carbonate can fill the pores inside the cement on the one hand, and on the other hand, it can also undergo electrolysis to become calcium ions and carbonate ions to generate calcium aluminate. Since the decomposition temperature of calcium aluminate is higher than that of calcium sulfoxide, it helps to improve the high temperature resistance of the grouting material;
[0103] S6. Pour the first mixed solution and the second mixed solution into the composite cementing base material and stir evenly at a stirring rate of 300 rpm for 4 minutes to obtain a high ground temperature resistant ultra-high flow nano-modified polymer grouting material.
[0104] S7. Replace the high ground temperature resistant ultra-high flow nano grouting material obtained in S6 with a polymer grouting material and place it in a curing box with a curing temperature of 20°C (curing humidity of 98%) for curing until it is taken out after the corresponding age for subsequent mechanical properties testing and microscopic properties testing.
[0105] Example 2
[0106] This embodiment provides a high temperature resistant ultra-high flow nano-modified polymer grouting material and a preparation method thereof. The raw materials of the grouting material are the same as those in Example 1, and the preparation method is the same as that in Example 1. The only difference is that the curing temperature in S7 is 50°C (curing humidity is 90%).
[0107] Example 3
[0108] This embodiment provides a high temperature resistant ultra-high flow nano-modified polymer grouting material and a preparation method thereof. The raw materials of the grouting material are the same as those in Example 1, and the preparation method is the same as that in Example 1. The only difference is that the curing temperature in S7 is 80°C (curing humidity is 80%).
[0109] Example 4
[0110] This embodiment provides a high temperature resistant ultra-high flow nano-modified polymer grouting material and a preparation method thereof. The grouting material is made of the following raw materials in parts by weight:
[0111] 500 parts of cement, 350 parts of fly ash, 35 parts of silica fume, 30 parts of calcium hydroxide, 15 parts of sodium carbonate, 1 part of tannic acid, 0.4 parts of cellulose nanofiber, and the water-cement ratio is 0.5.
[0112] The preparation and curing methods of the high temperature resistant ultra-high flow nano-modified polymer grouting material in this embodiment are the same as those in Example 1.
[0113] Example 5
[0114] This embodiment provides a high temperature resistant ultra-high flow nano-modified polymer grouting material and a preparation method thereof. The grouting material is made of the following raw materials in parts by weight:
[0115] 500 parts of cement, 400 parts of fly ash, 50 parts of silica fume, 45 parts of calcium hydroxide, 25 parts of sodium carbonate, 2 parts of tannic acid, 1.25 parts of cellulose nanofibers, and the water-cement ratio is 0.5.
[0116] The preparation and curing methods of the high temperature resistant ultra-high flow nano-modified polymer grouting material in this embodiment are the same as those in Example 1. The humidity in brackets in Examples 1-3 is the upper limit of the humidity at the current temperature, and the curing humidity difference does not affect the high temperature resistance of the high temperature resistant ultra-high flow nano-modified polymer grouting material of the present invention.
[0117] Comparative Example 1
[0118] Same as Example 1, except that tannic acid is not added.
[0119] Comparative Example 2
[0120] Same as Example 1, except that no cellulose nanofibers are added.
[0121] Comparative Example 3
[0122] Same as Example 2, except that tannic acid is not added.
[0123] Comparative Example 4
[0124] Same as Example 2, except that no cellulose nanofibers are added.
[0125] Comparative Example 5
[0126] Same as Example 3, except that tannic acid is not added.
[0127] Comparative Example 6
[0128] Same as Example 3, except that cellulose nanofibers are not added.
[0129] Comparative Example 7
[0130] Same as Example 1, except that tannic acid and cellulose nanofibers are not added.
[0131] Comparative Example 8
[0132] In this comparative example, the grouting material is made of the following raw materials in parts by weight: 500 parts of cement, 375 parts of fly ash, 42.5 parts of silica fume, 37.5 parts of calcium hydroxide, 20 parts of sodium carbonate, 5 parts of tannic acid, 0 parts of cellulose nanofibers, and the water-cement ratio is 0.5.
[0133] The preparation and curing methods of the grouting material in this comparative example are the same as those in Example 1.
[0134] Comparative Example 9
[0135] In this comparative example, the grouting material is made of the following raw materials in parts by weight: 500 parts of cement, 375 parts of fly ash, 42.5 parts of silica fume, 37.5 parts of calcium hydroxide, 20 parts of sodium carbonate, 0 parts of tannic acid, 3.2 parts of cellulose nanofibers, and the water-cement ratio is 0.5.
[0136] The preparation and curing methods of the grouting material in this comparative example are the same as those in Example 1.
[0137] When there is no tannic acid and cellulose nanofibers (i.e., comparative example 7), the silicate hydration and aluminosilicate polymerization process are shown in Figure 1 , the silicate hydration and aluminosilicate polymerization processes when tannic acid and cellulose nanofibers are added are shown in Figure 2 It can be found that the cementing particles will react immediately after contact with water, generally decomposing Ca 2+ and SiO 4 2-, hydration reaction with free water to form CSH gel, or polymerization reaction under alkali excitation to form CASH gel, thereby achieving the effect of filling pores and improving strength. However, as the reaction proceeds, part of the CSH gel will be adsorbed on the surface of the particles to hinder further reaction. Therefore, in the later stage of hydration, there will still be incompletely hydrated particles and pores inside. When tannic acid and cellulose nanofibers are added, tannic acid can be adsorbed on the surface of the cementing particles to form a hydroxyl layer, which hinders the Ca inside the particles. 2+ and SiO 4 2- At the same time, the hydroxyl groups can interact with Ca 2+ and SiO 4 2- The hydration reaction generates CSH and other substances, which wraps the cementing particles with a gel layer, further hindering the Ca 2+ and SiO 4 2- Since tannic acid requires Ca to slow down the setting 2+ The participation of alkali has little effect on the polymerization reaction to form CASH gel under alkali excitation. At this time, the alkalinity in the solution system is regulated so as not to react quickly, and the continuously generated CASH gel is sufficient to strengthen the grouting material. The specific reaction mechanism is shown in Figure 3 and Figure 4 At the same time, since tannic acid particles can be adsorbed on the surface of cellulose nanofibers, the interaction between particles is reduced, and the agglomeration phenomenon is reduced, so that the cellulose nanofibers can better play a bridging effect and fill the internal pores. Therefore, the porosity of the late hydration of cellulose nanofibers with tannic acid and cellulose is lower than that of the late hydration of cellulose nanofibers without tannic acid and cellulose nanofibers.
[0138] According to GB / T 1346 standard, the initial setting time, final setting time, initial fluidity and fluidity after curing for 60, 120 and 180 minutes were tested, and the compressive strength at 3d, 7d and 14d was tested according to GB / T 17671-2021. The test results are shown in Tables 1 and 2.
[0139] Table 1
[0140]
[0141] Table 2
[0142]
[0143] Figure 5-Figure 7The XRD analysis in the results revealed the hydration products produced by the neat grouting material at different curing days and temperatures. The results showed that the diffraction peak intensities of calcium hydroxide (CH), quartz and calcite were the highest, indicating that these substances dominated the neat grouting material. It is worth noting that despite the addition of tannic acid (TA) and cellulose nanofibers (CNFs), no new diffraction peaks were observed, indicating that these additives did not lead to the formation of new hydration products. By analyzing the diffraction peaks of calcium hydroxide and quartz, the early hydration reaction rate of the grouting material can be evaluated. Calcium hydroxide can undergo secondary hydration reaction with highly active silica inside silica fume to generate hydrated calcium silicate, thereby improving the compressive strength of the grouting material. With the extension of curing time, the content of calcium hydroxide and quartz gradually decreased, indicating that the rate of secondary hydration reaction was accelerating. This phenomenon shows that with the increase of curing age, calcium hydroxide and quartz in the neat grouting material participated in more secondary hydration reactions, resulting in a decrease in their relative content.
[0144] By comparing the XRD images of the grouting materials prepared in each embodiment at different curing temperatures, it can be found that with the increase of the curing temperature, the content of calcium hydroxide and quartz in each embodiment group becomes lower and lower. It means that with the increase of the curing temperature, the faster the secondary hydration reaction rate inside the grouting material, the higher the strength of the grouting material slurry, which also corresponds to the results of the compressive strength part. At the same time, by observing the amount of calcium sulfonate generated at different temperatures, it can be found that with the increase of the curing temperature, the content of calcium sulfonate inside the grouting material slurry becomes lower and lower. The main reason is that calcium sulfonate will decompose at 60°C, obvious thermal decomposition will occur at 70-75°C, and it will become an amorphous structure at 80°C. Therefore, it is found that the peak value of calcium sulfonate is getting lower and lower in the corresponding XRD spectrum, which also confirms this conclusion.
[0145] Since calcium silicate hydrate is an amorphous gel, and XRD mainly observes the internal crystalline phase, it is more difficult to observe calcium silicate hydrate. Since the purpose of generating calcium silicate hydrate is mainly to fill the internal pores or cracks, the amount of calcium silicate hydrate generated can be confirmed by the change in porosity. In order to verify the above theory, MIP data will be supplemented for verification in the future.
[0146] The hydration reaction rate of the grouting material is relatively fast in the early stage, so the change of porosity will be relatively more obvious. Therefore, the present invention selects the change of porosity at 20°C, 50°C and 80°C at 3d to verify the theory.
[0147] At temperatures below 40 °C, the addition of cellulose nanofibers (CNFs) can take advantage of their high aspect ratio and large specific surface area to more effectively fill the pores and promote the formation of hydration products, thereby reducing the pore size. Figure 8 and Fig. 9 As shown, the results of mercury injection testing and Figure 5 The XRD analysis results of Comparative Example 2 and Example 1 are consistent. On the contrary, the addition of tannic acid will lead to an increase in porosity, which is mainly because the adsorption and retarding effect of tannic acid reduces the formation of early hydration products, resulting in the failure of the hydration products that should have blocked the pores to form, thereby increasing the porosity. 3 S and C 2 This is consistent with the results of the higher peak of S, indicating that the addition of tannic acid affects the formation of products during the hydration process of the grouting material.
[0148] When the curing temperature is higher than 50°C, it can be found that the porosity of the composite doped with tannic acid and cellulose nanofibers is lower than that of the single doped cellulose nanofibers group (see Figure 10-13 ). The main reason is that when the temperature is high, the hydration reaction inside the grouting material is accelerated, resulting in excessive internal hydration heat and insufficient time for orderly precipitation. The hydration products may overlap disorderly, resulting in excessive micropores, resulting in reduced strength in the later stage. However, tannic acid will slow down the hydration reaction of the grouting material, reduce the early hydration heat, reduce the number of pores, and help optimize the internal pores. This also corresponds to the results of the early compressive strength in Table 1.
[0149] Since calcium silicate hydrate has different morphological appearances at different curing ages and curing conditions, it can be divided into three types from high to low in terms of strength improvement: cluster, net and needle. In order to confirm the form of calcium silicate hydrate filling the pores inside the grouting material, the present invention will observe the morphology of calcium silicate hydrate and other substances inside to confirm its development form. At the same time, by observing the internal pores, the MIP data (i.e. Figure 8-Figure 13 ) are consistent.
[0150] Figure 14-Figure 22 The SEM images mainly compare the internal hydration products and pore distribution conditions at different curing temperatures at 3d. It can be found that when the curing temperature is 20℃, the sample exhibits a loose and porous structure, and the internal calcium silicate hydrate is mainly needle-shaped, and only a small part of the hydration products are adsorbed on the surface of the fly ash. The reason is mainly due to the retarding effect of tannic acid, which reduces the hydration reaction rate and reduces the number of hydration products. When the curing temperature is 50℃ and 80℃, it can be found that the number of internal hydration products has increased significantly, and even the surface of the fly ash is completely wrapped by CSH and CASH, and the number of internal needle-shaped hydration products has also decreased significantly. On the one hand, this is because calcium sulfonate will decompose when the temperature is higher than 50℃ (however, CASH adsorbed on the surface of fly ash (aluminum-rich substance) has strong high temperature resistance and will not decompose at 80℃. The morphology of calcium sulfonate on the surface of aluminum-rich substance (fly ash) is shown in Fig.23). The main reason is that the mineral components inside the fly ash are alkali-activated to form a polymeric structure, which is more resistant to high temperatures. On the other hand, part of the CSH is also transformed from needle-shaped to cluster-shaped or grid-shaped, which has a more obvious effect on improving strength. At the same time, by comparing Comparative Example 6 and Example 3 at a curing temperature of 80°C, it can be found that the pores of Example 3 are significantly lower than those of Comparative Example 4, which can also explain that tannic acid can indeed reduce the phenomenon of increased rough pores caused by excessive hydration at high temperatures, which corresponds to the compressive strength results in Table 1.
[0151] The above are only preferred specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A high ground temperature resistant ultra-high flow nano-modified polymer grouting material, characterized in that: The raw material contains both tannic acid and cellulose nanofibers.
2. The high ground temperature resistant ultra-high flow nano-modified polymer grouting material according to claim 1, characterized in that: It is composed of the following raw materials: cement, fly ash, silica fume, calcium hydroxide, sodium carbonate, tannic acid, cellulose nanofibers and water; In terms of weight percentage, based on the weight of cement, the dosage of other components is as follows: The amount of fly ash added is 70%-80% of the weight of cement. The amount of silica fume added is 7%-10% of the weight of cement. The dosage of tannic acid is 0.2%-0.4% of the weight of cement. The amount of cellulose nanofiber added is 0.08%-0.25% of the weight of cement. The dosage of calcium hydroxide is 6%-9% of the weight of cement. The dosage of sodium carbonate is 3%-5% of the weight of cement; The water-cement ratio is 0.
5.
3. The high ground temperature resistant ultra-high flow nano-modified polymer grouting material according to claim 2, characterized in that: The amount of tannic acid added is 0.2%-0.3% of the weight of cement, and the amount of cellulose nanofiber added is 0.08%-0.16% of the weight of cement.
4. The high ground temperature resistant ultra-high flow nano-modified polymer grouting material according to claim 3, characterized in that: The amount of tannic acid added is 0.3% of the weight of cement, and the amount of cellulose nanofiber added is 0.16% of the weight of cement.
5. A method for preparing the high ground temperature resistant ultra-high flow nano-modified polymer grouting material according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1. Accurately weigh the raw materials according to the ratio, dry mix the cement, fly ash and silica fume, so that the three substances are evenly mixed to obtain a composite cementing base material for grouting material; S2. Divide the water into three equal parts, mix 1 / 3 of the water and tannic acid, stir evenly, and obtain a tannic acid solution; S3. Mix 1 / 3 of the water with the cellulose nanofibers and stir evenly to obtain a cellulose nanofiber solution; S4. The cellulose nanofiber solution and the tannic acid solution are stirred evenly, and after stirring, the mixture is allowed to stand to obtain a first mixed solution; S5. Mix 1 / 3 of water, sodium carbonate and calcium hydroxide to obtain a second mixed solution; S6. Pour the first mixed solution and the second mixed solution into the composite cementitious base material, stir evenly, and obtain a high ground temperature resistant ultra-high flow nano-modified polymer grouting material.
6. The method for preparing the high ground temperature resistant ultra-high flow nano-modified polymer grouting material according to claim 5, characterized in that: In step S2, the stirring rate is 300 rpm and the stirring time is 2 min.
7. The method for preparing the high ground temperature resistant ultra-high flow nano-modified polymer grouting material according to claim 5, characterized in that: In step S3, the stirring rate is 500 rpm and the stirring time is 2 min.
8. The method for preparing the high ground temperature resistant ultra-high flow nano-modified polymer grouting material according to claim 5, characterized in that: In step S4, the stirring rate is 300 rpm and the stirring time is 2 min; In step S5, the stirring rate is 300 rpm and the stirring time is 2 min.
9. The method for preparing the high ground temperature resistant ultra-high flow nano-modified polymer grouting material according to claim 5, characterized in that: In step S6, the stirring rate is 300 rpm and the stirring time is 4 min.
10. Application of the high geothermal resistant ultra-high flow nano-modified polymer grouting material according to any one of claims 1 to 4 in surrounding rock grouting under high geothermal environment, characterized in that: The high ground temperature environment is 40-80°C.
Citation Information
Patent Citations
Fiber concrete interface modifier and modification method
CN114315197A
Concrete for ultrahigh column and pouring method of ultrahigh column
CN117700183A
High-temperature-resistant high-strength resin blocking agent and preparation method thereof
CN119193122A
Cited By
Green mud jacking and grouting material based on industrial solid waste and preparation method of green mud jacking and grouting material
CN120423827A
Green press-slurry and grouting material based on industrial solid waste and preparation method thereof
CN120423827B
Dynamic-water dispersion-resistant grouting material for high-temperature water gushing plugging and preparation method of dynamic-water dispersion-resistant grouting material
CN121248235A